Prostitution as a Form of Human Alienation in Vargas Llosa's The Green House - Adhikari, Bam Dev (JODEM: Journal of Language and Literature, 2019)
The portrayal of prostitutes as the characters and prostitution as the institution is a rampant subject in Spanish American novels since the time of the first novelist of the continent, Jose Joaquin Fernandez de Lizardi. Mario Vargas Llosa’s novel The Green House portrays the women characters in pathetic exploitation, mainly sexual exploitation. The exploitation of the women in the novel is inextricably connected with the political system of Peru. The capitalist economic/ political system of Peru in the second half of the 20th century forced women to sell their body for their survival. Prostitution is treated as an industry from which the investors or the bidders earn surplus money. My argument is that the political/economic system, capitalism is responsible for the alienation and exploitation of women in Peru in the 1960s.